Assessment of A Patient with Liver Failure According to Marjory Gordon's Functional Health Pattern Model After Liver Transplantation from A Cadaver: Case Report - ilknur yücel (Nursing and Health Sciences Journal (NHSJ), 2023)
Liver failure, which is common worldwide, occurs as a result of a variety of causes, including obesity, liver disease, high alcohol consumption, hepatitis B or C infection, autoimmune disease, and iron or copper overload. With advanced liver failure, the most common cause of which is chronic viral hepatitis, liver transplantation is the only treatment of choice. Recurrent hepatitis C or B infections occur as a late complication after transplantation. Both can be treated well after a liver transplant. Other chronic liver diseases may also recur. The aim of this case report is to share our knowledge and experience about the disease and the case with our colleagues. The patient's data were collected according to M. Gordon's functional health patterns. Nursing diagnoses were determined according to the North American Nurses Association (NANDA) classification. The patient was 27 years old, male, single, had a university degree, and lived with his family in a large city. The patient, whose mother also had hepatitis B, had undergone liver transplantation in 2008. In December 2021, the patient was admitted to the gastroenterology department because of increased pruritus and icteric manifestations on the sclera. Nursing diagnoses: Risk of infection due to the inability of hepatic Kupfer cells to perform phagocytosis function, fatigue, ineffective individual coping, disturbed body image due to diffuse icteric appearance, impaired liver function, risk of impaired skin integrity, and lack of knowledge. The nursing process was applied according to the identified nursing diagnoses. The patient was discharged 7 days after hospitalization following the determination of drug levels. Patient care is extremely important in the nursing profession. Planning the patient's care according to M. Gordon's Functional Health Patterns Model and conducting data analysis in line with the model's sub-dimensions were observed to solve the patient's problems in a short time, and nursing care was provided to the patient in a systematic manner.